Determination of Different Saccharides Concentration by Means of a Multienzymes Amperometric Biosensor. (17th August 2017) - Portaccio, Marianna; Lepore, Maria
Abstract : A three-electrode amperometric biosensor for the detection of two different saccharides (lactose and glucose) in aqueous solutions is described. On the graphite working electrode, the glucose oxidase (GOD) and β -galactosidase ( β -gal) were coimmobilized by means of covalent bonding. The response of the biosensor as a function of the relative concentration of the two immobilized enzymes was investigated and the best working conditions were identified by measuring the sensitivity and the linear range response. In particular, our best lactose biosensor shows a linear range up to 0.010 mM and a limit of detection (LOD) and a sensitivity equal to 0.001 mM and 850 ± 81  μ A/mM, respectively. For glucose, the values of the above-mentioned parameters are equal to 0.015 mM for the linear range, 0.001 mM for LOD, and 505 ± 55  μ A/mM for the sensitivity. The working parameters of our biosensors are significant in comparison with other biosensors developed for concentration determination of the two saccharides investigated in the present work. In particular, low (LOD) and high sensitivities are obtained for lactose and glucose. To challenge our biosensor with real samples, it was tested using fruit juices, skim milk, and whey.